Estimation of permuting tri-homomorphisms and permuting tri-derivations associated with the tri-additive Υ-random operator inequality in matrix MB-algebra. Issue 6 (18th August 2022) - Aderyani, Safoura Rezaei; Saadati, Reza; Mesiar, Radko
Abstract : Applying the Radu-Miheţ method derived from an alternative FPT, we stabilize the tri-additive Υ-random operator inequality by providing a class of stochastic matrix control functions in matrix MB-algebras. In addition, we get an estimation for permuting tri-homomorphisms and permuting tri-derivations in unital matrix MC-⋄-algebras and matrix MB-algebras.